Effect of Quality Control and Production Process on Product Quality CV. Sumedang Tofu Factory - Evi Yulianti; Djoko Hananto (Eduvest - Journal of Universal Studies, 2025)
The purpose of this study was to determine how bedsar the effect caused on Quality Control and the Production Process on the quality of the products produced partially. Product Quality is the ability of a product to carry out its function, including durability, reliability, and other valuable attributes. In other words, production is said to be successful if it can produce quality products as expected. This study used a questionnaire method as an instrument. The respondents were 54 employees at CV. Sumedang Tofu Factory. And the sampling process is using saturated sampling technique using a quantitative approach that is associative in nature using primary data. With multiple linear regression analysis methods and data analysis techniques using SPSS Version 20. These results indicate that Quality Control has a positive and significant effect on product quality and the production process has no significant effect on product quality.